Bank Mini Syariah Laboratory Operations Management (Comparative Study of UIN Antasari Banjarmasin and UIN Sunan Ampel Surabaya) - Fithriana Syarqawie; Tuti Hasanah; Dessy Maulina; Syahrial Shaddiq (Graduate Program Magister Manajemen Pendidikan, 2024)
The Mini Sharia Bank Laboratory is a facility designed to provide students with practical experience in the field of sharia banking. The mini bank laboratory focuses on developing banking operational practicum activities within the Faculty of Islamic Economics and Business at UIN Sunan Ampel Surabaya and UIN Antasari Banjarmasin. The use of mini sharia banking laboratories by the two universities is intended to support lecture activities. The success of the Bank Mini Syariah laboratory cannot be separated from a well-running operational management system. This research aims to set up a management laboratory for Bank Mini Syariah UIN Antasari Banjarmasin to improve quality with a comparative study of Bank Mini Syariah UIN Sunan Ampel. This research uses a field approach with a qualitative approach through observation, interviews and documentary studies. The data analysis technique used is to explain patterns or categories, looking for relationships between various concepts. The results of the research found that there are several factors that influence the operational management of the mini sharia bank laboratory at UIN Antasari Banjarmasin and UIN Sunan Ampel Surabaya, namely internal factors, human resources, infrastructure, facilities and managerial, while external factors are security and comfort and cooperation.